(untitled) (Acta Scientiarum. Agronomy, 2023)
A diagrammatic scale with five levels (0, 0.1 – 2.0, 2.0 – 6.0, 6.0 – 10, and 10 – 14) was developed and evaluated to measure the symptoms of heat injury in a coffee seedling canopy. The scale was constructed to increase assessment efficiency and align the estimations more closely with the actual values. Two assessments with the diagrammatic scale and one without were conducted with an interval of seven days. The evaluators using the proposed scale presented estimates with better levels of precision, accuracy, reproducibility, and repeatability than those using a conventional method. The proposed diagrammatic scale was shown to provide a reliable estimate for assessing the symptoms of heat injury on the canopy of in Coffea arabica L. seedlings. Therefore, it is possible to standardize heat injury evaluation methods using this diagrammatic scale, allowing for data comparisons with different cultivars.